EFFECT OF PRE-AGEING THERMAL CONDITIONS ON THE CORROSION PROPERTIES OF ANTIMONY-MODIFIED Al-Si-Mg ALLOY (Nigerian Journal of Technology, 2015)
The purpose of this investigation was to evaluate the effect of pre-ageing thermal conditions on the corrosion properties of antimony-modified Al-Si-Mg alloy.The alloy was subjected to a Single Thermal Ageing Treatment; STAT (T6 temper-solution heat treatment and ageing) and Double thermal ageing treatment; DTAT (T7 temper- solution heat treatment and ageing for stabilization). These consist of solution heat treatment (SHT) at 540oC for 1hr, water quenched followed by an artificial ageing; DTAT and STAT. For the single thermal ageing treatment (STAT), quenched samples were aged at temperatures of 1800C for 2hrs, before cooling in air. In the double thermal ageing treatment (DTAT), quenched samples were pre-aged at a temperature of 90oC, 105oC and 120oC for 1- 5 hrs. This was followed by ageing at 180oC for 2hrs before cooling in air. The corrosion characteristic of the as-cast, Single Thermal Ageing Treatment (STAT) and Double Thermal Ageing Treatment (DTAT) were evaluated using weight loss and linear polarization techniques in a static 3.5%NaCl solution. From the results, the corrosion rate decreases with increasing pre-ageing time and temperatures. Equally, from the linear polarization data/curves, the corrosion rate of the treated alloy decreases at all ageing temperatures along with the ageing time. The Optical Microscope (OM) results of as-corroded samples revealed that the alloy suffers pitting/uniform corrosion. The corrosion behaviour of the DTAT samples in simulated seawater showed an excellent improvement in corrosion resistance than the as-cast and conventional STAT alloy.  http://dx.doi.org/10.4314/njt.v34i4.6